1992
DOI: 10.1083/jcb.116.2.405
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for isolation of cDNAs encoding proteins affecting human intestinal epithelial cell growth and differentiation: characterization of a novel gut-specific N-myristoylated annexin.

Abstract: Abstract. The human intestinal epithelium is rapidly and perpetually renewed as the descendants of multipotent stem cells located in crypts undergo proliferation, differentiation, and eventual exfoliation during a very well organized migration along the crypt to villus axis. The mechanisms that establish and maintain this balance between proliferation and differentiation are largely unknown . We have utilized HT29 cells, derived from a human colon adenocarcinoma, as a model system for identifying gene products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 106 publications
0
57
0
1
Order By: Relevance
“…Outside the plant kingdom, the maize annexins are most similar to annexin XHIa, originally described as an intestine-specific form of human annexin I (Wice and Gordon, 1992). The association of this annexin with the apical membrane of secretory cells of the intestinal epithelium suggests a role in the secretory pathway, a finding that is made more compelling by the recent discovery of annexin XHIb .…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Outside the plant kingdom, the maize annexins are most similar to annexin XHIa, originally described as an intestine-specific form of human annexin I (Wice and Gordon, 1992). The association of this annexin with the apical membrane of secretory cells of the intestinal epithelium suggests a role in the secretory pathway, a finding that is made more compelling by the recent discovery of annexin XHIb .…”
Section: Discussionmentioning
confidence: 73%
“…The most similar nonplant annexin is the "intestine-specific" form of human annexin I, now classed as annexin XHIa (35% identity; see Figs. 1 and 2) (Wice and Gordon, 1992;. Expression in Escherichia coli yields a 34-kD protein on SDS-PAGE, which strongly cross-reacts with antibodies to coleoptile p33/p35 (data not shown).…”
Section: Lsolation Of Annexin C D N a Clonesmentioning
confidence: 99%
See 1 more Smart Citation
“…A putative phosphorylation site for protein kinase C, as well as casein kinase II, can be detected near the N-terminus. Between positions 265 and 272 the TLIRVIVTR sequence highly resembles the TLIRIVVTR motif, the actin bundling site of annexin II, that is also present in human annexin XIIIa Wice and Gordon, 1992). Further experiments are required to test whether AnnMs2 can bind to actin as was shown for tomato annexins p34 and p35 (Calvert et al, 1996).…”
Section: Resultsmentioning
confidence: 97%
“…Peptide sequences obtained from tomato (Smallwood et al, 1990), corn (Blackbourn et al, 19921, pea (Clark et al, 19921, and cotton (Andrawis et al, 1993) proteins a11 indicated a degree of primary sequence conservation between plant and animal annexins. In animal cells most of the annexins are acetylated on their N terminus, although there is one report of an annexin with a myristolated N terminus (Wice and Gordon, 1992). Most of the plant proteins are also N-terminally blocked, but the nature of chemical modification is unknown.…”
Section: Purlflcatlon a N D Biochemical Propertiesmentioning
confidence: 99%